LE HOW ARE TELEMEDICINE PATIENTS CHANGING? - CAYOL, Amandine (MEDECINE LEGALE DROIT MEDICAL, 2025)
The use of telemedicine, and in particular teleconsultation, has long been held back by the fear that it will make patients more vulnerable, more exposed to possible breaches of their health data, and more isolated, in a dehumanized health system. It has now become commonplace, following the health crisis linked to the Covid-19 pandemic, and is part of a transformation of the doctor-patient relationship. While it allows the latter to be more autonomous, it could nevertheless lead to fears of the advent of a “health consumer” patient, in an uberized health system.